The Reality Of The Agrarian Law: Can It Address ‎Indonesia’s Land Problems? - R. Mustar Lofi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The Basic Agrarian Law (UUPA) of 1960 was established as the primary legal framework to govern land ownership, control, and utilization in Indonesia. Its core objectives were to promote social justice, ensure legal certainty for all citizens, and enhance public welfare through equitable and sustainable land governance. However, despite being in force for over six decades, Indonesia still faces persistent and increasingly complex agrarian issues. These include overlapping land certificates, recurring land conflicts, inadequate recognition of indigenous land rights, and the inefficiency of the land administration system. This study aims to explore the central question: To what extent is the UUPA effective in resolving current land-related problems in Indonesia, and how does its legal framework compare to the more advanced land law systems of other nations? This research applies a normative legal method with a comparative approach, analyzing case studies of land disputes in Indonesia and drawing comparisons with the land law practices in Singapore, Malaysia, China, and the Philippines. Findings indicate that the UUPA suffers from significant structural weaknesses, particularly in recognizing customary land rights and establishing a coherent and transparent administrative structure. Therefore, while the UUPA remains a historical milestone in Indonesian land law, this article concludes that substantial reforms are urgently needed to align the law with current social demands, legal complexities, and the pressures of globalization in the 21st century.